A pluralistic approach to artificial intelligence: ethical and educational challenges in educational institutions - Pellegrini, Sara; Sebastiani, Riccardo; Ninassi, Patrizia; Lampis, Emanuela (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The study examines the perceptions of teachers and administrative staff in a comprehensive school in Sardinia, highlighting disparities in digital skills and the urgent need for targeted training. It emphasizes the potential of AI to personalize learning and optimize administrative processes, while addressing risks related to privacy, bias, and technological dependency. The research proposes an ethical and integrated approach to foster inclusivity and sustainability in educational contexts.